The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/app.33401
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of radical polymerization of glycidyl methacrylate initiated by multi‐site phase transfer catalyst–potassium peroxydisulfate in two‐phase system

Abstract: The kinetics of radical polymerization of glycidyl methacrylate, initiated by the free radicals formed in situ in the multi-site phase transfer catalyst (PTC), 1,1,2,2-tetramethyl-1-benzyl-2-n-propylethylene-1,2-diammonium bromide chloride-potassium peroxydisulfate system was studied in an aqueous-organic two-phase media at 60 C 6 1 C under inert and unstirred condition. The rate of polymerization (R p ) was determined at various concentrations of the monomer, initiator, catalyst, and volume fraction of aqueou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…The rate of polymerization was slightly increases and then reaches the constant values in the employed acid concentrations. A similar kind of observation was reported in the phase-transfer catalyzed polymerization of different vinyl monomers [33][34][35][36][37][38][39][40][41].…”
Section: Variation Of Ph On the R Psupporting
confidence: 77%
“…The rate of polymerization was slightly increases and then reaches the constant values in the employed acid concentrations. A similar kind of observation was reported in the phase-transfer catalyzed polymerization of different vinyl monomers [33][34][35][36][37][38][39][40][41].…”
Section: Variation Of Ph On the R Psupporting
confidence: 77%
“…It was found that the R p decreased in the following order: cyclohexanone [ ethyl acetate [ cyclohexane. An increase in the rate of polymerization was attributed to the increase in the polarity of the solvents, which facilitates greater transfer of peroxydisulfate ion from aqueous phase to organic phase [20][21][22][23][24][25][26]42] (Table 5).…”
Section: Role Of Organic Solvents Polarity On R Pmentioning
confidence: 99%
“…The benefits of multi-site PTC are: enhance the rate of reaction with less time consumption and it transfers more number of active species from aqueous phase to organic phase during the reactions in contrast with single site-PTC. The reports on multi-site phase transfer catalyst aided radical polymerization of different alkyl methacrylates were gradually blooming in recent years [20][21][22][23][24][25][26]. The acrylic esters especially methyl methacrylate (MMA) are commercially fascinating and significant functional monomer for the synthesis of acrylic resins and various polymers based on poly(methyl methacrylate) (PMMA) with tunable properties.…”
Section: Introductionmentioning
confidence: 99%
“…2). The monomer reaction order of unity has been reported for the phase transfer catalyst and PDS-aided polymerization of various vinyl monomers [26,28,30,34].…”
Section: Effect Of [Ba] On the Rate Of Polymerization (R P )mentioning
confidence: 99%
“…Recently, phase transfer-catalyzed polymerization of vinyl monomers was gaining remarkable interest [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Inspired by the versatile application of PTC, herein, we report the systematic kinetic study of radical polymerization of n-butyl acrylate using cetyltrimethylammonium bromide (CTMAB) as phase transfer catalyst and potassium peroxydisulphate (PDS) as water-soluble initiator in an ethyl acetate-water two-phase system.…”
Section: Introductionmentioning
confidence: 99%